Study of Some Infrared Spectrum Properties of Zinc Oxide Compound - Nassour, Farid (Latakia University Journal -Basic Sciences Series, 2021)
The study of transparent oxides (TCO) is of great scientific importance due to its wide scientific applications is done . Therefore, our study of some of the physical properties of zinc oxide compound . The measurement of the infrared spectrum shows seven vibrational frequencies . The most prominent of which are (1190, 2400, 2500, 3420, 3725 )cm-1 , The study showed the smallest value of the absorption refractive index which is n=1.277 corresponding to the vibrational threshold frequency ν=1190cm-1, and the smallest optical length L=0.027cm corresponding to the vibrational threshold frequency 3420cm-1, and the largest optical length L=0.104 corresponding to the vibrational threshold frequency ν=1190cm-1 . It also shows that the largest values for refractive index, attenuation coefficient and optical conductivity respectively are n=6.244, α=36.846cm-1 , σopt=0.627(Ωcm)-1 corresponding to the vibrational threshold frequency at ν=3420cm-1 .